Received Pronunciation (RP) development through teaching professionally focused English in interdisciplinary context - Emelianova, T.V. (Opción, 2020)
The research aims to demonstrate that mastering RP by law-students contributes to their advance in English-language interaction in international environment. The relevance and novelty of the study lie in teaching (based on the interdisciplinary approach) RP skills to Law Institute nonimmigrant students immersed in the nonlinguistic intercultural environment. The data revealed that for 25% of respondents, specific difficulties were caused by poly-stressed words having no accentuation coincidence in Russian and English, in particular, verbs with postpositive elements typical for the English language. The research conclusions highlight the necessity for the law students to master Received Pronunciation in using multisyllabic words.